Eksplorasi Pengembangan Dimensi Konseptual untuk Meningkatkan Efektivitas Pembelajaran SKI Kelas VIII di MTs Syi’ar Islam Maibit - Nurul Laela; Khotimatus Sa’adah (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This research is motivated by the learning of Islamic Cultural History (SKI) which still focuses on memorization so that students are not able to understand the relationship between events in depth. This study aims to describe the application of conceptual dimension development to increase the effectiveness of SKI learning in grade VIII at MTs Syi'ar Islam Maibit. The method used is descriptive qualitative through in-depth interviews, participatory observations, and documentation studies. The research informants included SKI teachers, grade VIII students, and deputy heads of madrasas in the curriculum field who were selected purposively. The results of the study show that students already recognize basic historical facts in the material of the Abbasid, Ayyubid, and Mamluk dynasties, but are still weak in understanding the interconnectedness of concepts, analyzing cause and effect, and connecting historical events to the broader social context. Conceptual dimension mapping reveals that the aspects that need to be improved the most are analytical skills and the ability to structure knowledge sequentially. This study concludes that strengthening the conceptual dimension through visual media, concept maps, and analytical activities can help students understand SKI material more deeply and make learning more active and meaningful for the formation of students' character.